ChemInform Abstract: Asymmetric Isothiourea‐Catalyzed Formal [3 + 2] Cycloadditions of Ammonium Enolates with Oxaziridines. Issue 48 (December 2015) - Smith, Siobhan R.; Fallan, Charlene; Taylor, James E.; McLennan, Ross; Daniels, David S. B.; Morrill, Louis C.; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract: The title process is investigated with racemic oxaziridine (II) under conditions A).